Unconventional superconductivity in chiral molecule-TaS2 hybrid superlattices - Wan, Zhong; Qiu, Gang; Ren, Huaying; Qian, Qi; Li, Yaochen; Xu, Dong; Zhou, Jingyuan; Zhou, Jingxuan; Zhou, Boxuan; Wang, Laiyuan; Yang, Ting-Hsun; Sofer, Zdeněk; et al. (Nature, 2024)
Chiral superconductors, a unique class of unconventional superconductors in which the complex superconducting order parameter winds clockwise or anticlockwise in the momentum space1, represent a topologically non-trivial system with intrinsic time-reversal symmetry breaking (TRSB) and direct implications for topological quantum computing2,3. Intrinsic chiral superconductors are extremely rare, with only a few arguable examples, including UTe2, UPt3 and Sr2RuO4 (refs. 4-7). It has been suggested that chiral superconductivity may exist in non-centrosymmetric superconductors8,9, although such non-centrosymmetry is uncommon in typical solid-state superconductors. Alternatively, chiral molecules with neither mirror nor inversion symmetry have been widely investigated. We suggest that an incorporation of chiral molecules into conventional superconductor lattices could introduce non-centrosymmetry and help realize chiral superconductivity10. Here we explore unconventional superconductivity in chiral molecule intercalated TaS2 hybrid superlattices. Our studies reveal an exceptionally large in-plane upper critical field Bc2,|| well beyond the Pauli paramagnetic limit, a robust π-phase shift in Little-Parks measurements and a field-free superconducting diode effect (SDE). These experimental signatures of unconventional superconductivity suggest that the intriguing interplay between crystalline atomic layers and the self-assembled chiral molecular layers may lead to exotic topological materials. Our study highlights that the hybrid superlattices could lay a versatile path to artificial quantum materials by combining a vast library of layered crystals of rich physical properties with the nearly infinite variations of molecules of designable structural motifs and functional groups11.